2019
DOI: 10.1371/journal.pone.0214271
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the complexity of mobility of older medical patients in routine practice: An ethnographic study in Denmark

Abstract: Aim Many older medical patients experience persistent functional limitations after hospitalization, such as dependency in activities of daily living, recurring fall incidents and increased mortality. Therefore, increased activity and mobilization during hospitalization are essential to prevent functional decline in older medical patients. No previous studies have explored how the social context influences how health professionals decide whether or not to mobilize patients. This qualitative study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(96 citation statements)
references
References 35 publications
3
91
0
2
Order By: Relevance
“…In line with this, nurses have previously been identified as the key health care professionals in promoting mobility in hospitalized patients as they are the health care professionals spending most time with the patients [ 49 ].Additionally, the perception that mobility, as part of patient care, must be undertaken by nurses is well in line with the professional roles historically undertaken by nurses and physicians, where nurses focus on the health and wellbeing of the individual patient, whereas physicians focus on diagnoses and ameliorating medical conditions [ 50 ]. This cultural and social understanding of the roles of different health care professionals could hinder patient mobility since physicians, as we found in this study, may expect nurses and therapists to undertake tasks concerning mobility, whereas nurses may not consider mobility their responsibility [ 19 , 51 ] and, therefore, infrequently initiate mobility [ 52 ] or refrain from doing so due to e.g., fear of patient falls [ 33 ]. Thus, mobility ends up between two stools.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with this, nurses have previously been identified as the key health care professionals in promoting mobility in hospitalized patients as they are the health care professionals spending most time with the patients [ 49 ].Additionally, the perception that mobility, as part of patient care, must be undertaken by nurses is well in line with the professional roles historically undertaken by nurses and physicians, where nurses focus on the health and wellbeing of the individual patient, whereas physicians focus on diagnoses and ameliorating medical conditions [ 50 ]. This cultural and social understanding of the roles of different health care professionals could hinder patient mobility since physicians, as we found in this study, may expect nurses and therapists to undertake tasks concerning mobility, whereas nurses may not consider mobility their responsibility [ 19 , 51 ] and, therefore, infrequently initiate mobility [ 52 ] or refrain from doing so due to e.g., fear of patient falls [ 33 ]. Thus, mobility ends up between two stools.…”
Section: Discussionmentioning
confidence: 99%
“…However, in line with this study, previous studies have reported that physicians seem to refrain from advising older adults to be physically active as part of their treatment [ 28 , 32 , 59 ]. In an ethnographic field study conducted as a baseline study for the WALK-Cph project, Kirk et al [ 19 ] found that different health care professionals attach different meanings to the concept of mobility. It was found that mobility of older medical patients is entangled in a network of different professional identities, which blur the responsibility for mobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Item 16a and 16b b (Table S2) AUS Australian, MET metabolic equivalent of task, MVPA moderate-to-vigorous physical activity, UK United Kingdom, US United States, WHO World Health Organization a Since conduct of this Delphi study, UK guidance has been replaced with a newer version of recommendations [41] that were not tested for consensus agreement on applicability to hospitalised older adults b denotes recommendations/targets that were revised from original draft statements in Round 4 that received responses of endorsement from ≥70% of respondents blurring of responsibilities [73,74]. All professional groups have expertise that can promote patient mobility and improve outcomes [75].…”
Section: Source Of Recommendationmentioning
confidence: 99%